Associations between dietary antioxidant vitamins and risk of glioma: an updated systematic review and meta-analysis of observational studies - Ni, Ya-Jun; Huang, Yi-Qian; Yu, Lin; Zhang, Xiao-Yan; Zhu, Qin; Shu, Long; Zhang, Lun (Frontiers in Nutrition, 2024)
Background: Epidemiological studies investigating the potential associations between antioxidant vitamins intake and risk of glioma have yielded inconsistent results. To address this, we carried out a systematic review and updated meta-analysis to explore the relationship between dietary antioxidant vitamins intake and risk of glioma.Methods:We comprehensively searched electronic databases including PubMed, Web of Science, Embase, Scopus, China National Knowledge Infrastructure (CNKI) and Wan fang Data from their inception to March 2024. We employed fixed-effects or random-effects models to estimate the pooled relative risks(RRs) and 95% confidence intervals(CIs) for the associations between dietary antioxidant vitamins intake and risk of glioma. Publication bias was assessed through the visual inspection of the funnel plots and quantified by the Begg's and Egger's tests. Heterogeneity across studies was assessed using the Cochran's Q test and I-square (I 2 ). Additionally, subgroup and sensitivity analyses were performed to explore potential sources of heterogeneity and evaluate the robustness of the results.Results: Overall, a total of fifteen articles involving 3,608 glioma cases and 771,930 participants were included in the final analysis. The pooled analyses revealed that the highest intake of vitamin C significantly reduced the risk of glioma (RR=0.78; 95%CI: 0.63-0.96; P=0.022), compared to the lowest intake. However, no significant associations were observed between vitamin A and vitamin E intake and the risk of glioma (P>0.05). Subgroup analyses revealed the inverse association between vitamin C intake and risk of glioma in the population-based case-control studies(RR=0.82; 95%CI: 0.68-1.00, P=0.049) and study quality <7(RR=0.52, 95%CI: 0.29-0.92, P=0.025).Our findings show that higher intake of vitamin C is strongly associated with a reduced risk of glioma, although a dose-response relationship was not evident. Future large-scale prospective studies are warranted to confirm these findings.